Geotechnics of organic soils and peat - Huat, Bujang B. K.; Prasad, Arun; Asadi, Afshin; Kazemian, Sina (CRC Press, Taylor & Francis Group, 2014)
Peat and organic soils commonly occur as extremely soft, wet, unconsolidated surficial deposits that are an integral part of wetland systems. These types of soils can give rise to geotechnical problems in the area of sampling, settlement, stability, in situ testing, stabilisation and construction. There is therefore a tendency to either avoid building on these soils, or, when this is not possible, to simply remove or replace soils, which in some instances can lead to possibly uneconomical design and construction alternatives. However, in many countries of the world, these soils cover a substantial land area and pressure on land use is resulting in ever more frequent utilisation of such marginal grounds.